Sohibu Baiti: Rebana dan Dakwah di Mandar (1990 – 2014) - Rosdiana Hafid; Syahrir Kila; Darman Manda; Ahmadin Ahmadin (Universitas Negeri Makassar, 2022)
Sohibu Baiti: Tambourines and Da'wah in Mandar (1990-2014). This research aims to determine the background of the establishment of the Sohibu Baiti tambourine group, the development of the Sohibu Baiti tambourine group, and the role of Sohibu Baiti in Da'wah and Culture in Mandar. The research method used in this study is a historical research method which includes heuristics, source criticism, interpretation, and historiography. In this study, the background of the establishment of Sohibu Baiti was the lack of knowledge of tambourine music among the Mandar people in particular. The development of this group started from inappropriate to performing in international activities. The role of this group has succeeded in carrying out propaganda and cultural symbols through the art of tambourine music and inspiring the emergence of similar groups. It can be said that the Sohibu Baiti group has contributed to the advancement of Mandar art, especially the art of tambourine. Sohibu Baiti: Rebana dan Dakwah di Mandar (1990-2014). Penelitian ini bertujuan untuk mengetahui latar belakang berdirinya kelompok rebana Sohibu Baiti, perkembangan kelompok rebana Sohibu Baiti, dan Peran Sohibu Baiti Dalam Dakwah dan Kebudayaan di Mandar. Metode penelitian yang digunakan pada penelitian ini adalah metode penelitian sejarah yang meliputi heuristik, kritik sumber, interpretasi, dan historiografi. Dalam penelitian ini diketahui bahwa latar belakang berdirinya Sohibu Baiti adalah untuk melestarikan kesenian music rebana dikalangan masyarakat Mandar pada khususnya. Perkembangan kelompok ini berawal dari sekitar tempatnya sampai pentas di kegiatan internasional. Peran kelompok ini telah berhasil melakukan syiar dakwah dan kebudayaan melalui kesenian musik rebana dan mengilhami kemunculan kelompok sejenis. Hal ini dapat disimpulkan bahwa keberadaan kelompok Sohibu Baiti ini telah berkonstribusi pada pemajuan kesenian Mandar khususnya kesenian rebana.